The Hesperiidae of the Penelan Forest (Pénéssoulou, Benin), with the list of rhopalocères met (Lepidoptera,Papilionoidea, Hesperiidae) - (:unkn) unknown (My University, 2020)
We have identified a high number of Hesperiidae (69 species) in the Pénélan forest, located in the municipality of Bassila (Arrondissement de Pénéssoulou), Department of Atacora, Benin. We represent them in full and put in appendix the list of the 272 rhopalocera met.
Keywords: African Research